A Distinct Genetic Cluster in Cultivated Chickpea as Revealed by Genome‐wide Marker Discovery and Genotyping. Issue 2 (1st July 2017) - Pavan, Stefano; Lotti, Concetta; Marcotrigiano, Angelo R.; Mazzeo, Rosa; Bardaro, Nicoletta; Bracuto, Valentina; Ricciardi, Francesca; Taranto, Francesca; D'Agostino, Nunzio; Schiavulli, Adalgisa; De Giovanni, Claudio; Montemurro, Cinzia; et al.
Abstract : The accurate description of plant biodiversity is of utmost importance to efficiently address efforts in conservation genetics and breeding. Herein, we report the successful application of a genotyping‐by‐sequencing (GBS) approach in chickpea ( Cicer arietinum L.), resulting in the characterization of a cultivated germplasm collection with 3187 high‐quality single nucleotide polymorphism (SNP) markers. Genetic structure inference, principal component analysis, and hierarchical clustering all indicated the identification of a genetic cluster corresponding to black‐seeded genotypes traditionally cultivated in Southern Italy. Remarkably, this cluster was clearly distinct at both genetic and phenotypic levels from germplasm groups reflecting commercial chickpea classification into desi and kabuli seed types. Fixation index estimates for individual polymorphisms pointed out loci and genomic regions that might be of significance for the diversification of agronomic and commercial traits. Overall, our findings provide information on genetic relationships within cultivated chickpea and highlight a gene pool of great interest for the scientific community and chickpea breeding, which is limited by the low genetic diversity available in the primary gene pool.